Updates to the modern diagnosis of GERD: Lyon consensus 2.0 - C Prakash Gyawali; Rena Yadlapati; Ronnie Fass; David Katzka; John Pandolfino; Edoardo Savarino; Daniel Sifrim; Stuart Spechler; Frank Zerbib; Mark R Fox; Shobna Bhatia; Nicola de Bortoli; et al. (My University, 2023)
The Lyon Consensus provides conclusive criteria for and against the diagnosis of gastro-oesophageal reflux disease (GERD), and adjunctive metrics that consolidate or refute GERD diagnosis when primary criteria are borderline or inconclusive. An international core and working group was assembled to evaluate research since publication of the original Lyon Consensus, and to vote on statements collaboratively developed to update criteria. The Lyon Consensus 2.0 provides a modern definition of actionable GERD, where evidence from oesophageal testing supports revising, escalating or personalising GERD management for the symptomatic patient. Symptoms that have a high versus low likelihood of relationship to reflux episodes are described. Unproven versus proven GERD define diagnostic strategies and testing options. Patients with no prior GERD evidence (unproven GERD) are studied using prolonged wireless pH monitoring or catheter-based pH or pH-monitoring off antisecretory medication, while patients with conclusive GERD evidence (proven GERD) and persisting symptoms are evaluated using pH-impedance monitoring while on optimised antisecretory therapy. The major changes from the original Lyon Consensus criteria include establishment of Los Angeles grade B oesophagitis as conclusive GERD evidence, description of metrics and thresholds to be used with prolonged wireless pH monitoring, and inclusion of parameters useful in diagnosis of refractory GERD when testing is performed on antisecretory therapy in proven GERD. Criteria that have not performed well in the diagnosis of actionable GERD have been retired. Personalisation of investigation and management to each patient’s unique presentation will optimise GERD diagnosis and management.